1973
DOI: 10.1177/030006057300100210
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Treatment of Trichomonal Vaginitis: A Comparison of Tinidazole and Metronidazole

Abstract: A randomized, comparative trial was carried out in 100 patients with trichomonal vaginitis to compare the efficacy and toleration of a single 2 g dose of tinidazole and metronidazole. Tinidazole produced parasitological cure in 94% of patients (47/50) and a satisfactory clinical response in 96% of patients (48/50); for metronidazole the figures were 64% (32/50) and 72% (36/50) respectively. Side-effects were reported by 52% of patients (26/50) on tinidazole and 82% of patients (41/50) on metronidazole. Severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…38,42 The agent has recently become available in the United States and is a reasonable alternative to metronidazole. 38 For certain intestinal pathogens, such as Trichomonas vaginalis, 38 Giardia lamblia, [39][40][41] and Entamoeba histolitica, 41,42 tinidazole appeared to be more efficacious than metronidazole. The current study showed that combination therapy with ciprofloxacin and tinidazole was generally well-tolerated and effective in treating the majority of patients with chronic refractory pouchitis.…”
Section: Discussionmentioning
confidence: 99%
“…38,42 The agent has recently become available in the United States and is a reasonable alternative to metronidazole. 38 For certain intestinal pathogens, such as Trichomonas vaginalis, 38 Giardia lamblia, [39][40][41] and Entamoeba histolitica, 41,42 tinidazole appeared to be more efficacious than metronidazole. The current study showed that combination therapy with ciprofloxacin and tinidazole was generally well-tolerated and effective in treating the majority of patients with chronic refractory pouchitis.…”
Section: Discussionmentioning
confidence: 99%
“…The largest trial of tinidazole treatment (2-g single oral dose) for trichomoniasis in women was a multicenter, open-label trial demonstrating parasitologic cure, as assessed by wet preparation, in 818 (95%) of 859 women [30]. Randomized controlled trials comparing tinidazole (2-g single oral dose) and either metronidazole (2-g single oral dose) or short-course metronidazole have demonstrated parasitologic cure rates of 86%-100% for tinidazole [31][32][33][34][35][36][37]. In these trials, the efficacy of tinidazole has been equivalent or superior to that of metronidazole.…”
Section: Treatmentmentioning
confidence: 99%
“…Tinidazole (2-g single dose) has been shown to have efficacy in a limited number of cases of documented TV after divideddose metronidazole therapy of unspecified length (2 of 2 cases cured) and standard 7-day metronidazole therapy (13 of 14 cases cured) (table 1) [31,35]. Although the incidence of highlevel metronidazole resistance appears to be low, several case series have been published since 2000 documenting cases of metronidazole treatment failure, with the largest case series study reporting on 24 cases [44].…”
Section: Treatmentmentioning
confidence: 99%
“…Tinidazole is generally more expensive, reaches higher levels in the serum and the genitourinary tract, has a longer half-life than metronidazole (12.5 hours versus 7.3 hours), and has fewer gastrointestinal side effects [662][663][664] . In randomized clinical trials, the recommended metronidazole regimens have resulted in cure rates of approximately 84-98% [665][666][667] , and the recommended tinidazole regimen has resulted in cure rates of approximately 92-100% 666,[668][669][670][671] . Randomized controlled trials comparing single 2 g doses of metronidazole and tinidazole suggest that tinidazole is equivalent or superior to metronidazole in achieving parasitologic cure and resolution of symptoms 672 .…”
Section: Alternative Regimenmentioning
confidence: 99%